Students' Beliefs About the Nature of Intelligence (Mindset). Issue 4 (July 2022) - de Kraker-Pauw, Emmy; van Wesel, Floryt; Krabbendam, Lydia; van Atteveldt, Nienke
Important adolescents' career-related decisions might be influenced by their beliefs about malleability of intelligence and learning (mindset). We combined quantitative and qualitative data to provide in-depth insights in the beliefs that 13- and 14-year olds hold about learning and intelligence, the factors influencing these beliefs, and the consequences of these beliefs in relation to classroom behavior and study choices. To establish students' mindsets quantitatively, we categorized theory of intelligence (TOI) questionnaire averaged scores into three levels: entity, intermediate, or incremental mindsets, to provide insight into the distribution of the different mindset types in our sample ( N = 492). The results of this quantitative study show that more than half of the students believed intelligence is "fixed" (entity mindset), these data showed no effect of gender. To gain more in-depth insight in the views of these students, focus groups about mindset and its influences and consequences were held in a subsample ( n = 176). The qualitative data provide more nuanced insights, for example, they reveal subtle gender differences regarding effort beliefs and motivation. Integrated discussion of the quantitative and qualitative results demonstrates that this multimethod approach reflects the complexity of the concept mindset better than only the widely used TOI questionnaire.